CHILD-FRIENDLY SCHOOL MANAGEMENT IN IMPROVING STUDENT CHARACTER AT MIS AEK RIUNG SIGAMBAL SCHOOL - Fitri Hafni Siregar (Jurnal Scientia, 2022)
This research is a qualitative research in the form of a case study. This research was conducted at MIS Aek Riung Sigambal. There is still a school atmosphere that has not become a comfortable and fun place for children. There are still acts of violence committed by students, there are still acts of bullying, crime, smoking, brawls and cheating is still found by schools during exams. Therefore, a Child Friendly School (SRA) program is needed. The purpose of this study is to implement the Child Friendly School program and develop the character of students at MIS Aek Riung Sigambal. The respondents of this study were principals and teachers. The results of this study are the policy of child-friendly schools at MIS Aek Riung Sigambal encourages all school members to care about the school environment and to be anti-violent so that the atmosphere at school becomes healthy, safe and comfortable. MIS Aek Riung Sigambal has implemented child-friendly education, that the school has attempted various programs and activities in implementing child-friendly education. Although schools have made efforts to implement child-friendly education as best as possible, it is still said to be not optimal.